Analisis Perilaku Kerja Petani Sayur di Kelurahan Maharatu Kecamatan Marpoyan Damai Kota Pekanbaru - Agsriyani, Dwi; Edwina, Susy; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research was to determine the effect of individual variables, organizational variables and psychology variables working for farmers. The author took hypothesized that individual, organizational and psychology variables simultaneously or partially have a positive and significant effect on the behavior of farmers in sub Maharatu. The research method is used descriptive an quantitative methods of statistical analysis using linier regression. The data used primary and secondary. Researchers used 70 vegetables farmers in the sample. The studyâ€™s results shows that the individual, organizational and psychology variables simultaneously and partially have a slight positive and significant influence on the behavior of vegetable growers working in Maharatu Village, Marpoyan Damai Subdistrict, Pekanbaru City. Of the coefficient of determination is known that the contribution of the influence of individual, organizational and psychology variables of the work to 58,2 % while the remaining 41,7 % is influenced by other variables not included in this models. Â Keywords : Individual, organizational, psychology, working behavior Â